The effectiveness of nutritional Counselling for diabetic patients In outpatient dietetic clinic, HUSM: a preliminary study - Harith, Sakinah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
To exam1ne with randomized controlled design whether one-to-one nutritional counseling by dietitian for diabetic patients type 2 can improve their health outcomes using Diet Management Tool (DMT)